Factors Related To Bone Structure and Pain in The Spine in Traditional Diamond Mine Workers - Agusta, Martin (Pusat Publikasi Nusantara, 2025)
Pain in the spine are the most common disease among informal or unorganized sector workers. This can happen because in the informal sector the use of work ergonomics has not been applied properly, which results in changes in bone structure and pain in the spine. The purpose of this study was to determine the factors associated with bone structure and pain in the spine complaints in Sungai Tiung Traditional Mine workers, Cempaka District, Banjarbaru City, South Kalimantan. This research is a quantitative observational analytic study with cross sectional design. The subjects of this study were traditional diamond mining workers. The sample of this study was 95 people who were sampled using accidental sampling. The instruments used included questionnaires, Nordic Body Map (NBM) worksheets, Ovako Working Analysis System (OWAS), and LMM Key Method. Data analysis used chi square statistical tests and fisher exact test (CI = 95%, ? = 0.05). Results: Statistical test results showed that there was no relationship between age (p-value 0.921), work posture (p-value 0.509), and smoking status (p-value 0.707) with bone structure and pain in the spine complaints, while there was a relationship between manual handling activities (p-value 0.010) with bone structure and pain in the spine complaints. Manual handling activities in traditional diamond mining workers have a relationship with bone structure and pain in the spine complaints, while age, smoking status, and work posture in traditional diamond mining workers have no relationship with bone structure and pain in the spine complaints.